Exploring the use of POLY4 for the improvement of productivity, peanut quality, and soil properties in Southern India - Gopinath, Kodigal A.; Rajanna, Gandhamanagenahalli A.; Visha Kumari, Venugopalan; Singh, Vinod Kumar; Ajay, B. C.; Awasthi, Neeraj K.; Mishra, Vipin; Sukumaran, Suvana; Venkatesh, Govindarajan; Rajkumar, Bollam (Frontiers in Plant Science, 2024)
Polyhalite-based POLY4, a multi-nutrient source containing potassium, calcium, magnesium, and sulphur, is increasingly recognised for its potential to improve crop yields and soil health in agricultural systems. It is also been considered as a feasible approach for addressing the deficiency in potassium, calcium, and sulphur within a single application source. The present study aimed to investigate the impact of polyhalite-based POLY4 application, either as a complete or partial substitute for traditional potassium fertiliser and gypsum supplement, on the improvement of peanut (Arachis hypogaea) growth and soil quality. An extensive field study was conducted from 2021 and 2022, employing ten distinct nutrient management treatments with three replications in a randomised complete block design. The findings of the study indicated that the application of polyhalite (POLY4) in conjunction with only NP fertilisers resulted in a higher yield advantage (approximately 150–200 kg ha-1) than in plots treated with NPK + gypsum (at 500 kg ha-1) and control plots. The application of polyhalite-based fertiliser (POLY4) at a rate that was 100% equivalent to K along with NP fertilisers resulted in a significant increase in pod yield (5.3–12.8%) over NPK + gypsum and control plots. Thus, the increased crop yield led to an increase in gross returns of 4.88% and in net returns of 4.28% with the application of POLY4 (100%) + NP fertilisers over other treatments. Likewise, variable rates of conventional fertilisers along with POLY4 (100% recommended) + NP + gypsum at 310 kg/ha significantly increased the linoleic acid content (38.5%), oleic acid content, and oil content (48.1%) by reducing palmitic acid (11.96%) content in the groundnut seed. Interestingly, POLY4 use at the 50% recommended rate also resulted in yields that were comparable with those obtained with 100% NPK. Therefore, applying POLY4, a polyhalite fertiliser, in either a 100% or 50% equivalent of essential K can be an effective way of increasing the production of peanut crops and promoting agricultural sustainability.